The McMaster Polarized Ion Source - McKay, Wallace John (My University, 1976)
The theory of the Lamb-Shift, Spin-Filter polarized ion source is discussed. The design and construction of such as source for the McMaster University Tandem Accelerator is described. Finally, measurements and calibrations of the operating parameters are presented.
Keywords: Physics; Physics